KONSEP PENGEMBANGAN POTENSI SEKTOR EKONOMI TERHADAP UPAYA PENINGKATAN PERTUMBUHAN EKONOMI DI PROVINSI GORONTALO TAHUN 2012-2016 - Ismail A. Ibrahim (International Interdisciplinary Conference on Sustainable Development Goals, 2018)
The aims of this study are to analyze the potential of the economic sector in the development of Gorontalo Province and to identify potential economic sectors that have competitive advantages and specialization in Gorontalo Province. Data collection methods were obtained through secondary data, that is from documents in the relevant agencies. The method used is LQ (location Quotient) analysis to identify economic sectors in the development of Gorontalo Province, identify potential sectors that have competitive advantages, assisted with time series data that looks at GRDP growth between the study area and reference area. The results of the study showed that in Gorontalo Regency on the period of 2012-2016 which became the main base sector was the agricultural sector while for Gorontalo City the main base sectors were electricity gas and water supply sector, building sector, hotel and restaurant trade sector. In addition, those sectors contributed as the most contributor to GRDP and absorb labor in the regency and cities so that it can encourage the development of GRDP in each year in Gorontalo Province.